Tinjauan: Malondialdehyde (MDA) sebagai Marker Stres Oksidatif Berbagai Penyakit - Gusnirwan, Alief; Sangging, Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2024)
Oxidative Stress is a condition of imbalance between free radicals and antioxidants in the body. This can be caused by the excessive production of reactive oxygen species (ROS) or reactive nitrogen species (RNS), which can damage biomolecules such as lipids, proteins, and nucleic acids. Various factors, including environmental elements like UV rays, radiation, pollutants, smoking, heavy metals, and exposure to drugs, can trigger this condition. Malondialdehyde (MDA) serves as a stable and accurate biomarker of oxidative stress and can indicate the oxidation processes within cell membranes. Elevated concentrations of MDA are associated with pathological conditions and can lead to damage to blood vessel walls, the development of heart diseases, changes in cell membrane properties, and DNA mutations, contributing to the formation of cancer and genetic diseases. Numerous studies have shown significantly different MDA levels between healthy individuals and those with specific diseases, and MDA values correlate with the severity of various illnesses. Understanding the mechanisms of oxidative stress and measuring biomarkers like MDA provide crucial insights into the role of oxidative stress in the pathology of diverse diseases, opening avenues for the development of more effective prevention and treatment strategies.